Synthesis, in silico studies and antibacterial activity of some novel 2-substituted benzimidazole derivatives - Ramakrishna Chintakunta; Geethavani Meka (SpringerOpen, 2020)
Abstract Background The o-phenylenediamine is a versatile starting material for several compounds. Synthesized o-phenylenediamine and amino acids (glycine, alanine, aspartic acid, and l-proline) undergo condensation via Phillips reaction. The synthesized compound showed the promising antibacterial activity of Bacillus subtilis and Pseudomonas aeruginosa at the concentration of 100, 50, 25, 12.5, 6.25, 3.12, 1.6, 0.8, 0.4, and 0.2 μg/ml. Ciprofloxacin was used as standard drug. Synthesis of benzimidazole derivatives was carried out and purified by recrystallization process using ethanol. Substituted derivatives were characterized by melting point, TLC and spectroscopic methods include FT-IR and 1H-NMR. Results In silico studies were adopted for synthetic derivatives by Molinspiration, ChemDraw, and online software tool. Minimum inhibitory concentration (MIC) values of B. subtilis and P. aeruginosa were reported, and benzimidazole ligands and Molinspiration scores were generated and listed. Conclusion The more negative values indicate a higher binding affinity. The generated ligand observations can be visualized. Physical constants of synthesized derivates such as solubility and melting point were determined. Bioactivity scores were noted for different derivatives and predicted percentage absorption in the gut. The antibacterial activity was performed using the MIC method (aerobic).